2011
DOI: 10.1111/j.1537-2995.2011.03175.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood management in pediatric spinal deformity surgery: review of a 2‐year experience

Abstract: Transfusion requirements in scoliosis patients are dependent on blood loss as determined by Cobb angles and number of segments fused relative to the patients' blood volume as determined by weight. Implementation of a blood management protocol resulted in a low transfusion rate and unexpectedly led to the preoperative diagnosis of a number of patients with low levels of von Willebrand activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 42 publications
10
65
0
8
Order By: Relevance
“…A greater number of levels instrumented and increased operative time likely indicate a more complex procedure that could be associated with a greater number of postoperative issues, such as pain management and prolonged rehabilitation. A greater number of levels fused also has been associated with increased blood loss and thus, need for a blood transfusion, which could prolong LOS [11,17,54]. There may be a benefit to reducing operative blood loss in order to reduce postoperative LOS.…”
Section: Discussionmentioning
confidence: 99%
“…A greater number of levels instrumented and increased operative time likely indicate a more complex procedure that could be associated with a greater number of postoperative issues, such as pain management and prolonged rehabilitation. A greater number of levels fused also has been associated with increased blood loss and thus, need for a blood transfusion, which could prolong LOS [11,17,54]. There may be a benefit to reducing operative blood loss in order to reduce postoperative LOS.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, surgical and anesthetic techniques have changed significantly, making the current value of these studies limited. In a recent retrospective cohort review of neuromuscular and idiopathic scoliosis patients, Hassan et al [53] reported that a modern comprehensive blood management protocol (which included hypotensive anesthesia) led to 1.7 % blood transfusion rate (versus 36 %) in AIS patients. The value of each component cannot be determined from this study.…”
Section: Supporting Empirical Evidencementioning
confidence: 99%
“…Previous reports from Hassan et al [10] and our institutional reference range of 58-150 % for VWF: RCo. All patients in the database with VWF: RCo ≤70% were identified.…”
Section: Study Design and Matchingmentioning
confidence: 99%
“…One previous study indicated that patients with patients with levels <70 were prone to higher blood losses while undergoing PSF [10]. Scoliosis is managed by a team that often includes a blood management protocol (see Appendix 1) [10,11]. This includes preoperative measurement of VW antigen, VWF: RCo and hematology referral for those with borderline low activity levels circa 30 % or if the preoperative data was suggestive of a bleeding tendency.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation